Collocation Models of Neologisms in Modern Armenian Language - MELKONYAN, LUIZA (Bulletin of Yerevan University B: Philology, 2021)
From the set collocations, only the compound names and phraseological expressions are considered in the article. In connection with the social structure changes in the last decade the necessity to express new establishments and new concepts with compound names, has considerably increased. The newly-formed collocations with noun value, with full or partial copying, are mostly binary or ternary formations. Among the compound names, there are a large number of names of enterprises, firms, organizations, parties, etc. In the system of set collocations, the phraseological expressions are unique units. Among the newly-formed phraseological expressions casual, colloquial, jargon structures are also found. Among the newly-formed collocational expressions, there are such, one of the components of which appears in the collocation with a new meaning and that meaning change is visible only in set collocations.